How do adult-oriented coaching practices change over time and correspond with changes in key criterion outcomes? An 8-week study - Motz, D.; Young, B. W.; Rathwell, S.; Callary, B. (International Sport Coaching Journal, 2024)
The Adult-Oriented Sport Coaching Survey assesses how often coaches use practices tailored to adult and older adult athletes. Cross-sectionally, said practices contribute to a quality masters sport experience for masters athletes (MAs); however, the stability of adult-oriented coaching over time and whether changes in coaching over time correspond with psychosocial outcomes for MAs is unknown. Therefore, coaches (N = 32; Mage = 49.0) and MAs (N = 103; Mage = 51.5) completed the Adult-Oriented Sport Coaching Survey twice 8 weeks apart. MAs also completed criterion measures for facets of the coach-athlete relationship, basic needs satisfaction, and thwarting. Our first question was whether mean group values for adult-oriented coaching changed over time. Repeated measures analysis of variance demonstrated stability of coaches` and MAs` scores. Our second question was whether changes in adult-oriented coaching corresponded with changes on criterion measures. Path analyses showed increased perceived frequency of adult-oriented coaching that, generally, was associated with enhancing three facets of the coach-athlete relationship, relatedness satisfaction, autonomy satisfaction, and reducing competency thwarting. The discussion centers on how adult-oriented coaching might facilitate quality sporting relationships, empowerment, and mastery in adult sport programming. These nonintervention results are interpreted with an eye toward considerations in future Adult-Oriented Sport Coaching Survey-based coaching interventions.